Emotional Intelligence as a Buffer: Mitigating the Impact of Job Stress on Researcher Performance - Aldo Agustianus; Tulus Budi Sulistyo Radikun; Windi Ayu Diningsari (International Journal of Psychology and Health Science, 2026)
This study aims to examine the role of emotional intelligence in moderating the relationship between job stress and researcher performance at a research institution in Indonesia. This study is a correlational study using a survey method. A total of 142 researchers from one of the research institutions in Indonesia were obtained using a convenience sampling technique. Three instruments were used, namely the Effort–Reward Imbalance Questionnaire (ERI) to measure job stress, the Wong and Law Emotional Intelligence Scale (WLEIS) for emotional intelligence, and the Individual Work Performance Questionnaire (IWPQ) for researcher performance. Data analysis was carried out using correlation analysis and moderated regression analysis using the Jamovi application version 2.6.25. Based on the correlation analysis, the results showed that job stress correlated negatively with performance significantly (r = -0.33, p < 0.05). This indicates that the more a researcher is given work pressure, the more their performance decreases. Emotional intelligence correlated positively with performance (r = 0.64, p < 0.05). This indicates that the higher a researcher's emotional intelligence, the greater their performance. The results of the moderation regression analysis indicate that emotional intelligence does not act as a moderator (b = 0.11, p > 0.05). Based on these results, it can be concluded that emotional intelligence did not buffer the negative effect of job stress on performance. Therefore, to improve researcher performance, it is necessary to decrease the level of job stress.